Thermal and electrical properties of carbon nanotubes purified by acid digestion - Yuca, Neslihan; Karatepe, Nilgün; Yakuphano?lu, Fahrettin (My University, 2011)
Carbon nanotubes (CNTs) possess unique structural, mechanical, thermal and electronic properties, and have been proposed to be used for applications in many fields. However, to reach the full potential of the CNTs, many problems still need to be solved, including the development of an easy and effective purification procedure, since synthesized CNTs contain impurities, such as amorphous carbon, carbon nanoparticles and metal particles. Different purification methods yield different CNT characteristics and may be suitable for the production of different types of CNTs. In this study, the effect of different purification chemicals on carbon nanotube quality was investigated. CNTs were firstly synthesized by chemical vapor deposition (CVD) of acetylene (C 2H 2) on a magnesium oxide (MgO) powder impregnated with an iron nitrate (Fe(NO 3) 3·9H 2O) solution. The synthesis parameters were selected as: the synthesis temperature of 800°C, the iron content in the precursor of 5% and the synthesis time of 30 min. The liquid phase oxidation method was applied for the purification of the synthesized CNT materials. Three different acid chemicals (HNO 3, H 2SO 4, and HCl) were used in the removal of the metal catalysts from the synthesized CNT material to investigate the possible effects of each acid solution to the purification step. Purification experiments were carried out at two different temperatures (75 and 120 °C), two different acid concentrations (3 and 6 M) and for three different time intervals (6, 8 and 15 h). A 30% H 2O 2: 3M HCl (1:1 v%) solution was also used in the purification step to remove both the metal catalysts and the amorphous carbon. The purifications using this solution were performed at the temperature of 75°C for 8 hours. Purification efficiencies at different conditions were evaluated by thermogravimetric analysis. Thermal and electrical properties of CNTs were also determined. It was found that the obtained electrical conductivity values for the carbon nanotubes were typical for organic semiconductor materials and thermal stabilities were changed depending on the purification chemicals.
Keywords: Acid digestion; Carbon nanotubes; Electrical conductivity; Purification; Thermal stability